Study of the photocrosslinking of some photocrosslinkable systems based on glycydyl ether of o-crezolformaldehyde resin. III - Influence of some plasticizers on the photocrosslinking of the CG-BCDE-TAS systems - Hiền, Lê Xuân; Minh, Đỗ Thị Ngọc; Triều, Nguyến Thị Việt (Vietnam Journal of Chemistry, 2012)
The influence of some plasticizers such as cashew nut shell oil (CNSO), castor oil (CO), epoxidized soya–bean oil (ESBO) and diocthylphtalat (DOP) on the photocrosslinking of the photocrosslinkable systems on the base of glycydyl eter of o–crezolformaldehyde resin (CG), Biscycloaliphatic diepoxy (BCDE) monomer, triarylsulfonium salt (TAS) have been studied. In the systems, the content of the plasticizers were 15% of the total mass of CG, BCDE and the content of TAS was 5% of the total mass of CG, BCDE, plasticizer. The mass ratio CG/BCDE was 60/40 and 40/60 for the systems containing CNSO, CO, DOP and ESBO respectively. During photocrosslinking of the 20 mm thickness film of the systems under 250 mW/cm2 intensity UV–lamp, the fastest rate of conversion and the highest final conversion of TAS were observed in the system without plasticizers, while the fastest rate of conversion and the highest final conversion of epoxy groups were observed in the system with the presence of CO. The obtained results were explained by the difference of the chemical structure of the plasticizers which influenced on the polarity of the photocrosslinking systems.